(untitled) (REMUNOM, 2025)
This paper examines the configurations of psychosis in contemporary times, focusing on the differences between classical psychosis and ordinary psychosis. The aim is to connect these conceptualizations with the transformations of the contemporary master’s discourse, in order to understand their effects on the subjectivity of the time. The work revisits Freud’s formulations, which conceived of psychosis as the result of the self’s radical rejection of incompatible representations, leading to a rupture with reality and the creation of a new internal reality marked by hallucinations and delusions. Lacan, in revisiting the Freudian concept of Verwerfung, reformulates it as foreclosure, understanding psychosis based on the absence of the Name-of-the-Father signifier in subjective structuring, a signifier that introduces the function of paternal interdiction. Based on these foundations, the concept of ordinary psychosis is considered as a way to understand contemporary clinical manifestations in their diagnostic subtlety, given the pluralization of Names-of-the-Father and psychiatric diagnoses. At the same time, it is important to emphasize that the modes of relationship between the subject and the social Other, the constitution of the symptom, and its connection with unconscious knowledge are intimately linked to the scientific development of each era. Thus, if in the past, hysterical paralysis was related to advances in neurology, in contemporary times, depression, anorexia, drug addiction, and ordinary psychoses emerge as symptomatic responses to social transformations. These manifestations can be understood as a result of the decline of ideals sustained by the Other, the imperative of consumption, and the strengthening of neuroscientific discourse, which guides pharmaceutical production. Thus, it is evident that cultural and scientific changes directly impact the configuration of contemporary subjectivity.